Effect of load–distributing devices on the stability of heavy vehicles. (4th August 2014) - Kack, Benoit; Richard, Marc J.
This article presents a mathematical model of a load–transferring device integrated to an existing computer–based mathematical method for predicting the directional response of trucks and tractor–trailers. It also considers some of the key simulations to assess the important case of a loaded tractor semi–trailer using a load distributing device at high speeds (75 to 100 km/h). The use of the device in that case is an effective anti–rollover mechanism. However, the lane change manoeuvres showed to generate an highly unstable behaviour for the vehicle.